Description of some classes of Leibniz algebras - Rakhimov, Isamiddin Sattarovich; Rikhsiboev, Ikrom Mirzarustamovich; Khudoyberdiyev, Abror Khakimovich; Karimjanov, Ikboljon Abdulazizovich (Elsevier, 2012)
In this paper we describe the isomorphism classes of finite-dimensional complex Leibniz algebras whose quotient algebra with respect to the ideal generated by squares is isomorphic to the direct sum of three-dimensional simple Lie algebra sl2 and a three-dimensional solvable ideal. We choose a basis of the isomorphism classes' representatives and give explicit multiplication tables.